Study on Dye-sensitized Solar Cells based on ZnO Nanorods and Graphene Enhanced P3HT as HTM - Mahdi , Samir (University of Thi-Qar Journal of Science, 2019)
A quasi solid state dye-sensitized solar cells (DSSC) is fabricated using 1-propyl-3methylimidazolium iodide and Poly (3-Hexail Thiophene) P3HT, and P3HT-loading graphene (G) as the composite electrolyte. The electrolyte without added iodine is sandwiched between ZnO NW photo electrode both pristine and graphene enhanced P3HT (G-P3HT, 5% wt graphene) were used in solid state dye as Hole transport material draw a lot of attention due to easy fabrication, using P3HT-Graphene (P3HTI-graphene) nanocomposites were synthesized on FTO glass by solution process and employed as HTM to replace the conventionally used expensive Pt electrode, The solar cells based on vertical ZnO nanowire arrays by utilizing a mixture paste of LiI, PMII and solid iodine as electrolyte. The initial results showed the power conversion efficiency of 2.1%. The cells with pristine and G-P3HT showed different performance. The power conversion efficiency was improved from 0.16 to 2.1 mA for G-P3HT solar cells. It exhibited increased power conversion efficiency from 0.87 to 2.1%